186 Partial loss of AKAP1 promotes cardiac dysfunction, gut barrier abnormalities, and alteration of gut microbiota composition during ageing. (8th December 2021) - D'Apice, Stefania; Paolillo, Roberta; Coretti, Lorena; Esposito, Giovanni; Lembo, Francesca; Perrino, Cinzia
Abstract: Aims: Mitochondrial A-kinase anchoring proteins (mitoAKAP) encoded by the Akap1 gene promote Protein Kinase A mitochondrial targeting, regulating mitochondrial structure and function, reactive oxygen species production, and cardiomyocyte survival. Whether mitoAKAP levels play a role in cardiac ageing, gut barrier integrity and gut microbiota composition is currently unknown. The aim of this study was to highlight the complex interplay between cardiac dysfunction, gut barrier integrity, gut microbiota composition and ageing in young (6-month-old, 6 m) and old (24-month-old, 24 m) wild type ( wt ) and Akap1 heterozygous mice ( Akap1 +/− ). Methods and results: Cardiac function was noninvasively analysed by echocardiography in 6 m and 24 m wt and Akap1 +/− mice. Gut microbial DNA was extracted and gut microbiota composition was analysed by Illumina Mi-Seq analysis. Bioinformatics analysis was carried out to identify major intestinal populations. Alpha diversity within each sample was determined, and then analysed according to genotype and age; then, inter-sample diversity was determined. For each dataset, we used UniFrac to calculate the differences between microbial communities based on phylogenetic distance between taxa sets in a phylogenetic tree. Bioinformatics analyses were performed using the analysis of similarities (ANOSIM). To evaluate the role of mitoAKAPs in intestinal permeability, we analysed intestinal junction proteins expression levels in colon samples of all groups. Variance analysis was performed to determine significance among the groups. Partial loss of Akap1 accelerated the progression of cardiac dysfunction in 24 m mice, as demonstrated by a significantly lower % fractional shortening (%FS) compared to 24 m wt mice (%FS, wt 6 m: 60 ± 3; Akap1 −/+ 6 m: 58 ± 5; wt 24 m: 49 ± 6*; Akap1 −/+ 24 m: 39 ± 12*§; * P  < 0.05 vs. wt 6 m; § P  < 0.05 vs. wt 24 m). In 24 m Akap1 +/− mice, ageing was associated to enhanced colon permeability, as shown by reduced levels of Ocln and Tjp1 mRNA expression. A principal Co-ordinate analysis of faecal samples based on their unweighted UniFrac distances revealed that samples from Akap1 +/− 24 m mice cluster apart from wt 24 m samples, suggesting that Akap1 +/− 24 m mice exhibit a different assortment of microbial communities. This observation was supported by ANOSIM R statistic that revealed significant differences in gut microbiota composition between wt and Akap1 +/− 24 m mice (ANOSIM R = 0.475, P  = 0.023), while no significant differences in bacterial assortment were identified between wt and Akap1 +/− 6 m mice. We analysed the differences in abundance of all 2042 Operational Taxonomic Units (OTUs) between age-matched wt and Akap1 +/− . We identified 10 OTUs differently represented in wt and Akap1 +/− 6 m mice, while a bigger set of bacterial OTUs (19) were different between wt and Akap 1 +/− 24 m mice. Consistent with previous results in patients with heart failure, we identified Clostridiales, Blautia producta, and R. Torques among differently regulated species. These results are in accordance with previous data on patients with heart failure (HF). Conclusions: Partial Akap1 deletion plays an important role in the progression towards HF and modulates colon permeability and gut microbiota composition during ageing. This work highlights the complex interplay between gut microbiota and development of cardiac dysfunction, and characterization of these processes might lead to the development of new diagnostic and therapeutic approaches for cardiac dysfunction.